ERM PT. BEC FEED SOLUTIONS INDONESIA (JEB17 : Jurnal Ekonomi dan Bisnis, 2023)
Enterprise risk management (ERM) aims to build corporate value which is a picture of how the glory or welfare of its stakeholders is. Therefore, company risk management is very influential on the smooth running of a company's activities. This study reviews the Implementation of Enterprise Risk Management at PT. BEC Feed Solutions Indonesia. This study aims to determine the risks that exist in PT. BEC Feed Solutions Indonesia, and the ERM process at PT. BEC Feed Solutions Indonesia. This type of research is descriptive qualitative research through case studies. This research is based on primary data and secondary data. Primary data was obtained from interviews and documentation, while secondary data was obtained from the official website of PT BEC Feed Solution Indonesia and several other supporting journals. The results of the research we got concluded that PT BEC Feed Solutions Indonesia is experiencing a risk of a Global Economy Crisis. To overcome this risk Where will PT. BEC Feed Solutions Indonesia will carry out mitigation which will be borne and faced by the company to keep its Cash Flow safe. In addition, the company also shares risks with investors. Handling the risk of Global Economy Crisis at PT. BEC Feed Solutions Indonesia is carried out by a President Director from Australia, assisted by a President Director from Indonesia and assisted by managers in each division to ensure all risks are managed safely and controlled effectively.